Las piedras suplican auxilio. Arqueólogos, huaqueros y autoridades locales en Chavín de Huántar (1870-1945) - Hernández Asensio, Raúl (2012)
This study delves into the complex exchange between professional archeologists,local specialists, huaca looters, travelers, local intellectuals, public officials, and political authorities over the value of Chavín de Huántar between 1870 and 1945. Stakeholders had different objectives, strategies, and interests. An insight into this interweaving of relationships is key to understanding the discourses and practices that were an integral part of the development of archeology in Peru in its initial phase.